2000
DOI: 10.4049/jimmunol.164.2.1046
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-Activated Receptor γ Does Not Inhibit IL-6 or TNF-α Responses of Macrophages to Lipopolysaccharide In Vitro or In Vivo

Abstract: We have investigated the potential use of peroxisome proliferator-activated receptor γ (PPARγ) agonists as anti-inflammatory agents in cell-based assays and in a mouse model of endotoxemia. Human peripheral blood monocytes were treated with LPS or PMA and a variety of PPARγ agonists. Although 15-deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) at micromolar concentrations significantly inhibited the production of TNF-α and IL-6, four other high affinity PPARγ ligands failed to affect cytokine production. Similar resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
115
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(127 citation statements)
references
References 45 publications
(51 reference statements)
7
115
4
Order By: Relevance
“…Earlier studies have demonstrated that 15d-PGJ 2 could suppress expression of several genes in PMA-activated monocytes/ macrophages, including those coding for inducible NO synthase, TNF-␣, IL-1␣, IL-6, and gelatinase B/matrix metalloproteinase-9 (7,8,12). However, other studies showed that activation of PPAR␥ did not inhibit the production of proinflammatory cytokines induced by LPS stimulation (13). Therefore, whether 15d-PGJ 2 and its synthetic analogs can be safely used as antiinflammatory agents remains elusive.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Earlier studies have demonstrated that 15d-PGJ 2 could suppress expression of several genes in PMA-activated monocytes/ macrophages, including those coding for inducible NO synthase, TNF-␣, IL-1␣, IL-6, and gelatinase B/matrix metalloproteinase-9 (7,8,12). However, other studies showed that activation of PPAR␥ did not inhibit the production of proinflammatory cytokines induced by LPS stimulation (13). Therefore, whether 15d-PGJ 2 and its synthetic analogs can be safely used as antiinflammatory agents remains elusive.…”
Section: Discussionmentioning
confidence: 85%
“…These observations raise the possibility that 15d-PGJ 2 may be a potential therapeutic compound for treatment of inflammatory diseases. However, other studies have failed to observe an inhibitory effect of 15d-PGJ 2 on induced expression of TNF-␣ and IL-6 in freshly prepared human monocytes/macrophages (13). Thus, whether 15d-PGJ 2 will be of therapeutic value as an antiinflammatory agent remains controversial.…”
mentioning
confidence: 91%
“…inflammatory effects (Thieringer et al, 2000;Guyton et al, 2001;Moore et al, 2001b;Fu et al, 2002). Thus, PPARs have been shown to have in vivo relevance with inflammatory processes, and that is the reason why the mechanisms underlying these effects are highly interesting to clarify.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that 15deoxy-PGJ 2 was more effective than synthetic PPAR␥ ligands in reducing the expression of iNOS and cytokines by monocytes (27). It has been shown that high concentrations of thiazolidinedione antidiabetic drugs are re-quired to obtain antiinflammatory activities.…”
Section: Discussionmentioning
confidence: 99%